2004
DOI: 10.1111/j.1439-0426.2004.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Some biological characteristics of the garfish (Belone belone L., 1761) in Izmir Bay, Aegean Sea

Abstract: The present work was aimed at determining the growth parameters of the garfish, Belone belone, a commercially important pelagic fish species in Izmir Bay (Aegean Sea). A total of 347 garfish specimens was collected during the period January-December 1997 from purse-seine boats operating in Izmir Bay. Fork length and total weight of the specimens ranged from 26.0 to 54.5 cm and from 16.51 to 281.73 g, respectively. Maximum age group determined was V for females and IV for males. Female : male ratio was 1 : 0.45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
3
18
1
Order By: Relevance
“…Thus, Dorman (1991) reported that the range of matured oocytes diameter was between 0.1 and 3.0 mm with a mean value of 2.0 mm. Uçkun et al (2004) found that the average diameter of matured oocytes was 1.84 mm, while the minimum and maximum diameter was 0.4 and 4.0 mm, respectively. For the garfish population that inhabits the Baltic Sea, average egg diameter 3.27 ± 0.15 mm (range: 2.95-3.70 mm) is reported by Korzelecka-Orkisz et al (2005).…”
Section: Histologymentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, Dorman (1991) reported that the range of matured oocytes diameter was between 0.1 and 3.0 mm with a mean value of 2.0 mm. Uçkun et al (2004) found that the average diameter of matured oocytes was 1.84 mm, while the minimum and maximum diameter was 0.4 and 4.0 mm, respectively. For the garfish population that inhabits the Baltic Sea, average egg diameter 3.27 ± 0.15 mm (range: 2.95-3.70 mm) is reported by Korzelecka-Orkisz et al (2005).…”
Section: Histologymentioning
confidence: 94%
“…In comparison with the previous studies (Yüce 1970;Bedoui et al 2002;Fehri-Bedoui and Gharbi 2004;Sinovčić et al 2004;Uçkun et al 2004;Samsun et al 2006), the length range of Fig. 7 Images of garfish gonad tissue: a ripe female (marked oocytes of three different development stages were v-maturing oocytes or oocytes in the stage of vitellogenesis in which the yolk granules that appeared first in the periphery of the cytoplasm increased in size and number dispersing within the cytoplasm, mn-ripe oocytes in which the fusion of several oil droplets resulted in the formation of a large oil droplet, which migrated towards animal pole together with the nucleus and hy-''hydrated oocyte'' in which the yolk granules fused forming a continuous mass of fluid yolk and with its formation the spawning is initiated), b ripe male (marked cells were SPSpermatocytes-small oval cells; ST-Spermatids-cells with larger and rounded nucleus and SZ-Spermatozoa-the cells developed from spermatids when they were rejected into the cyst cavity as the spermatogenesis was coming to an end) garfish specimens in the present study is the widest reported till now for garfish specimens inhabiting the Adriatic Sea, Mediterranean and Black Sea.…”
Section: Length Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Embryonic and larval development of B. belone was also studied under laboratory conditions (Dulčić et al, 2009;Kužir et al, 2009). Spawning time based on gonadosomatic index and fecundity of B. belone was studied in the Turkey's Aegean Sea coasts by Uçkun et al (2004) and in the Bosporus by Yüce (1975). Moreover, only one study of B. euxini spawning time and absolute fecundity features was carried out for population in the middle Black Sea (Samsun et al, 2006).…”
mentioning
confidence: 99%